Self-Inflicted Industry Wounds: Early Warning Signals and Pelican Gambits. (January 2013) - Donaldson, Thomas; Schoemaker, Paul J.H.
Systemic risks arising from underlying interdependences can create havoc at an industry level and are often too formidable for any single firm to manage. The contagion effects of these risks, including the recent financial crisis, offshore oil spills, and the Japanese nuclear disaster, have upended industry practices. Sometimes they have even pulled economies apart at the seams. We recommend that leaders heed models of cooperative behavior found in nature by engaging in "Pelican Gambits, " which we define as strategic moves towards cooperation in highly competitive economic environments for the purpose of limiting risk to one's firm, the industry and society.